Brexit, Human Rights and the Role of Constitutional Culture - Oliva, Javier García (Revista de Investigações Constitucionais, 2019)
In order to fully explore this territory, it is essential to appreciate how both Brexit and Human Rights fit within the wider “Constitutional Culture” of the State. The article starts this discussion with an examination of what the concept of Constitutional Culture signifies, both generally, and also within the specific and idiosyncratic context of the United Kingdom. Then, it explores how human rights fit within British Constitutional Culture and assesses how the Brexit saga relates to both British Constitutional Culture and human rights as they exist within this paradigm. Having addressed the nature of British Constitutional Culture, the place of human rights within it and the impact of the Brexit process, the role of referenda in our democratic processes will be discussed, alongside the function of human rights, in sense of identifiable freedoms which can be named and asserted, within whatever form of new Constitutional Culture and settlement ultimately emerges.